Optimasi Kondisi Proses Maserasi Daun Strobilantes Cusia - Murni Yuniwati; Diny Fitri Lestari; Bambang Kusmartono; Paramita Dwi Sukmawati; Muhammad Yusuf (Jurnal Teknologi, 2022)
The process of taking natural dyes from strobilanthes cusia leaves in a very simple way is carried out at UMK Shiungu Temanggung. The process was carried out by soaking the leaves and twigs of the cusia strobilantes in water, with a time of 3 days, and a solvent-to-material ratio of 6:1. The raw materials in the form of intact leaves and twigs cause the maceration results to be less than optimal and cause waste in the form of leaves and twigs which are increasingly stinking. Starting from this problem, it is necessary to carry out research to be able to determine the best conditions for the dye collection process. The maceration process, which was carried out using intact leaves and twigs of Cusia strobilantes that were not chopped, with a maceration time of three days and a solvent-to-material ratio of 6:1, resulted in a solution with a very small absorbance value. For red color with a wavelength of 678 nm the solution has an absorbance value of 2.375. Whereas for the purple color with a wavelength of 409 nm the solution has an absorbance value of 5.275. In addition, the waste obtained is difficult to process because it is large and interlocking and smells bad so it disturbs the environment. Research on the process of maceration of Cusia strobilantes leaves with variations in leaf size, a ratio of solvent to material, and maceration time, shows that the smaller the size of the material and the greater the time used, the greater the absorbance value of the macerated solution, while the ratio of solvent to material indicates an optimal point. The best conditions chosen are process conditions that produce maximum maceration results and facilitate the waste treatment process